Diabetic retinopathy screening ratio is improved when using a digital, nonmydriatic fundus camera onsite in a diabetes outpatient clinic - Roser, Pia; Kalscheuer, Hannes; Gröner, Jan; Lehnhoff, Daniel; Klein, Roman; Auffarth, Gerd U.; Nawroth, Peter Paul; Schütt, Florian; Rudofsky, Gottfried (Journal of diabetes research, 2016)
To evaluate the effect of onsite screening with a nonmydriatic, digital fundus camera for diabetic retinopathy (DR) at a diabetes outpatient clinic.